Surviving the Diasporic Home: Renegotiating Homeland and Hostland in 20th-Century Indo-American Literature - Bera, Shreya (AMERICANA E-journal of American Studies in Hungary, 2019)
The paper aims to explore the transcultural aesthetics of Indian diaspora and its gradual transformation through 20th-century Indo-American literature while observing reconfiguration of the domestic boundaries in North America. Bharati Mukherjee, Jhumpa Lahiri and Chitra Banerjee Divakaruni explore the three-dimensional socio-political construction of home and re-read the themes of migration and resettlement. The intention is to showcase the relationship and co-existence between homeland and the hostland through a comparative study of selected works by these authors by focusing on the angle of ‘diasporic home’ through unfamiliarity, hostility, adaptation.